ADSORPTION PROPERTIES OF BIFUNCTIONAL SORBENTS OBTAINED BY MICROWAVE CARBONIZATION OF APRICOT KERNEL SHELLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The results of studying the physicomechanical and sorption properties of bifunctional sorbents obtained by chemical and electrochemical oxidation of the surface of carbonizates of apricot kernel shells are presented. It was shown that sorbents based on carbonizates obtained by microwave carbonization of shells, in comparison with sorbents obtained in the traditional way, are characterized by a more uniform pore distribution and a larger specific surface area and adsorption capacity.
Keywords: microwave carbonization, bifunctional sorbents, oxidized coals, sorption of heavy metals